ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT (STUDI EMPIRIS AUDITOR KAP DI JAWA TIMUR) - Retna Safriliana; Nancy Indah Susanti Boreel (Universitas Negeri Malang, 2016)
Premature sign off of audit procedure is one form of Reduced Audit Quality / RAQ behaviors. The objectives of this research are to analyze time pressure, audit risk, materiality, review and quality control procedures, self esteem in relation to ambition and turnover intentions that can affect the premature sign-off of audit procedures. The population of this study are auditors who haveworked at Public Accountant Firm in Jawa Timur . The sample of this research are 56 auditors who have worked for Public Accountant Firm at Surabaya and Malang.Collection of the data are using survey method by questionnaries. Analysis of the data are using logistic regression analysis test .The result of analysis showed that time pressure, audit risk, materiality, review procedures and quality control, self esteem in relation to ambition significantly influenced premature sign-off audit procedures. But turnover intentions don’t significantly influenced premature sign-off audit procedures.Keywords: Auditor, premature sign-off of audit procedures, time pressure, audit risk, materiality review procedures and quality control, self esteem in relation to ambition, turnover intentions